Postpartum unconscious dynamics emerging from the Lüscher color test in Ethiopian women. (18th June 2017) - Zanardo, Vincenzo; Gabrieli, Catia; Volpe, Francesca; Savio, Francesca; Straface, Gianluca; Soldera, Gino
Abstract: The aim of this study was to explore the feasibility of the Lüscher color test (LCT), a psychological instrument based on theory that colors are selected in unconscious way and that the color sensory perception of color is objective and universal. The research has involved 24 Ethiopian women, which delivered at the Getche Health Center in Gurage. It seemed to be relevant for the majority of Ethiopian women identify the rejected color (58.66%), the gray, than the favorite color, the yellow 33.33%). The yellow color suggests that they better express their personality in a physical context, while the gray color indicates that they want to live this experience intensely. This exploratory work lays the foundations for further studies in disadvantaged women, both in developing low-income Countries as well as in industrialized Countries characterized by an high level of emigration, and for clinical applications by the complete LCT version.